Goblet Cell Adenocarcinoma of the Appendix: A Systematic Review and Incidence and Survival of 1,225 Cases From an English Cancer Registry - Palmer, Kieran; Weerasuriya, Scott; Chandrakumaran, Kandiah; Rous, Brian; White, Benjamin E.; Paisey, Sangeeta; Srirajaskanthan, Rajaventhan; Ramage, John K. (Frontiers in Oncology, 2022)
Background Goblet cell adenocarcinoma of the appendix (GCA) is a rare and aggressive tumour with varying nomenclature and classification systems. This has led to heterogeneity in published data and there is a lack of consensus on incidence, survival and management. Methods We provide an overview of GCA with a comprehensive systematic review using PRISMA methodology and a retrospective analysis of all cases recorded in the English National Cancer Registration and Analysis Service database between 1995 and 2018. The Kaplan-Meier estimator was used to calculate overall survival and Cox proportional hazard regression was used to identify prognostic factors. Results The systematic review demonstrated an incidence of 0.05–0.3 per 100 000 per year amongst North American registry studies. 1-year, 3-year and 5-year survival was 95.5%, 85.9–87.6% and 76–80.6% respectively. Age, stage and grade were identified as prognostic factors for survival. Our analysis included 1225 cases. Age-standardised incidence was 0.0335 per year in 1995 and gradually rose to 0.158 per year in 2018. 1-year, 3-year and 5-year survival was 90.0% (95% confidence interval (95% CI): 85.4–94.0), 76.0% (95% CI: 73.8–80.9) and 68.6% (95% CI: 65.9–72.2) respectively. On univariate cox regression analyses, female sex, stage and grade were associated with worse overall survival. On multivariate analysis, only stage remained a statistically significant prognostic factor. Conclusions GCA of the appendix is rare, but incidence is increasing. We report a lower incidence and survival than North American registry studies. Higher stage was associated with decreased survival. Further prospective studies are required to establish optimal management.